Pengaruh Value dan Parent Attachment terhadap Career Maturity berdasarkan Persepsi Mahasiswa Angkatan 2017 di Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Metro - Saputra, Irfaan Hisyam; Fitriani, Fitriani (Universitas Muhammadiyah Metro, 2021)
This study aims to determine whether Work Values ​​and Parent Attachments affect Career Maturity in class 2017 students at the Faculty of Economics and Business, Muhammadiyah Metro University.This type of research is quantitative. With the purposive sampling technique, namely